Injectable in situ forming gel based on lyotropic liquid crystal for persistent postoperative analgesia. (February 2018) - Mei, Liling; Xie, Yecheng; Huang, Ying; Wang, Bei; Chen, Jintian; Quan, Guilan; Pan, Xin; Liu, Hu; Wang, Lili; Liu, Xianguo; Wu, Chuanbin
Graphical abstract: Abstract: Local anesthetics have been widely used for postoperative analgesia. However, multiple injections or local infiltration is required due to the short half-lives of local anesthetics after single injection, which results in poor compliance and increasing medical expense. In this study, an in situ forming gel (ISFG) based on lyotropic liquid crystal was developed to deliver bupivacaine hydrochloride (BUP) for long-acting postoperative analgesia. BUP-ISFG was designed to be administrated as a precursor solution which would spontaneously transform into gel with well-defined internal nanostructures for sustained drug release at the site of administration when exposed to physiological fluid. A lamellar-hexagonal-cubic phase transition occurred during the in situ gelation. The lamellar phase of the precursor solution endows it with low viscosity for good syringeability while the unique nanostructures of hexagonal and cubic phases of the in situ gel provide sustained drug release. Persistent analgesia effect in vivo was achieved with BUP-ISFG, and the plasma BUP concentration was found to be steadier compared to commercially available BUP for injection. In addition, the ISFG displayed acceptable biocompatibility and good biodegradability. The findings are positive about ISFG as a sustained release system for persistent postoperative analgesia. Statement of Significance: To address the issue of insufficient postoperative analgesia associated with short half-lives of local anesthetics after single injection, an in situ forming gel (ISFG) based on lyotropic liquid crystal was developed to deliver bupivacaine hydrochloride (BUP) for postoperative analgesia over three days. The results demonstrated that persistent analgesia effect in vivo was achieved with single injection of BUP-ISFG, and the plasma BUP concentration was found to be steadier compared to commercially available BUP injection. The BUP-ISFG possessed a lamellar-hexagonal-cubic phase transition with corresponding crystal change in 3D nanostructure during the in situ gelation. The relationship between crystal nanostructure and carrier function, might provide some insights to the design and clinical applications of the drug delivery systems based on lyotropic liquid crystal.